The Dual Dose-Dependent Effects of Corticosterone on Hippocampal Cell Apoptosis After Traumatic Brain Injury Depend on the Activation Ratio of Mineralocorticoid Receptors to Glucocorticoid Receptors - Zhang, Bin; Yang, Mengshi; Yan, Qiongyu; Xu, Xiaojian; Niu, Fei; Dong, Jinqian; Zhuang, Yuan; Lu, Shenghua; Ge, Qianqian; Liu, Baiyun (Frontiers in Pharmacology, 2021)
In our recent studies, we reported that mineralocorticoid receptor (MR) had the opposite effects of glucocorticoid receptor (GR) on neural cell survival after traumatic brain injury (TBI). However, whether short-term use of high-dose natural glucocorticoids, which are mixed agonists of both MR and GR, leads to neurotoxic effects by inducing excessive GR activation is unclear, as is the threshold GR activation level and the possible signaling pathways remain unclear. In this study, we examined the dual dose-dependent effects of corticosterone (CORT) on spatial memory, hippocampal cell survival and receptor-mediated downstream signaling pathways after TBI. We found that different doses of CORT exhibited dual effects on hippocampal cell survival and rat spatial memory. Low doses of CORT (0.3 and 3 mg/kg) significantly increased MR activation, upregulated Akt/CREB/Bad phosphorylation and Bcl-2 concentration, reduced the number of apoptotic neural cells, and subsequently improved rat spatial memory. In contrast, a high dose of CORT (30 mg/kg) exerted the opposite effects by overactivating GR, upregulating P53/Bax levels, and inhibiting Erk/CREB activity. The results suggest that the neuroprotective and neurotoxic effects of endogenous GC depend on a threshold level and that a higher dose of GC, even for short-term use, should be avoided after TBI.